2021
DOI: 10.2147/cmar.s319048
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Potential Prognostic Value of Peroxiredoxin 1 in Oral Squamous Cell Carcinoma

Abstract: The role of the peroxiredoxin (PRDX) family in oral squamous cell carcinoma (OSCC) remains unclear. This study aimed to investigate the expression of PRDXs and their effects on the prognosis in OSCC. Methods: The expression of PRDXs and their effects on prognosis were analysed in 216 OSCC samples from The Cancer Genome Atlas (TCGA) database. OSCC tissues and adjacent noncancerous tissues (ANTs) were obtained from 68 clinical patients. Quantitative real-time (qRT)-PCR, Western blot, and immunohistochemical (IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Although its role in diseases such as inflammation and cancer has been gradually elucidated as research has deepened, there have been a few studies exploring the expression and mechanism of Prdx1 in OSCC. In OSCC, increased levels of Prdx1 have been observed in previous studies [7,12], while contrasting findings have also been reported [27]. Prdx1 is elevated in oral leukoplakia and dysplastic oral keratinocytes and is crucial for the transformation of precancerous lesions into malignant cancer [28,29].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although its role in diseases such as inflammation and cancer has been gradually elucidated as research has deepened, there have been a few studies exploring the expression and mechanism of Prdx1 in OSCC. In OSCC, increased levels of Prdx1 have been observed in previous studies [7,12], while contrasting findings have also been reported [27]. Prdx1 is elevated in oral leukoplakia and dysplastic oral keratinocytes and is crucial for the transformation of precancerous lesions into malignant cancer [28,29].…”
Section: Discussionmentioning
confidence: 86%
“…The peroxiredoxin (Prdx) family, another vital oxidative defense system, that serves as the direct substrate of Trx, remains lacking in research. Prdx1 is the most studied among the Prdx family members, whose abnormal expression has been observed in various tumors and precancerous lesions, including OSCC [6,7], esophageal cancer [8], and others [8]. Cancer patients with stronger Prdx1 expression often suffer from worse outcomes [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate a close relationship between PRDX1 and other gastrointestinal cancers such as pancreatic cancer 74 , cholangiocarcinoma 75 , and oral cancer 76 . In pancreatic cancer, there is a significant elevation in PRDX1 expression levels, making it a viable therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…In cholangiocarcinoma, PRDX1 expression also significantly increases, influencing the occurrence and development of cholangiocarcinoma by regulating SNAT1 expression 75 . In oral cancer, PRDX1 is highly expressed and is significantly correlated with tumor staging, lymph node metastasis, and pathological grading, making it a promising biomarker for predicting lymph node metastasis and prognosis in oral cancer patients 76 . However, these gastrointestinal cancers have a relatively low incidence rate.…”
Section: Resultsmentioning
confidence: 99%